A VERY RARE CAUSE OF DIARRHEA IN A CHEMOTHERAPY-INDUCED NEUTROPENIC PATIENT: PELLAGRA - Fatma YILMAZ; Murat ALBAYRAK; Senem MARAL; Hacer Berna AFACAN ÖZTÜRK; Merih REİS ARAS; Pınar TIĞLIOĞLU; Mesut TIĞLIOĞLU; Buğra SAĞLAM (Hematology, Transfusion and Cell Therapy, 2021)
Case report: Pellagra is a systemic disease caused by a deficiency of vitamin B3 .A 19-year-old male patient, who was diagnosed with Burkitt's lymphoma was admitted to the hematology clinic for the second cycle of R-CODOX-M chemotherapy treatment. The patient at risk of malnutrition  developed dermatit,diare and demans  during treatment. The cause of diarrhea in the neutropenic patient is mostly in the form of infective diarrhea. Diarrhea due to vitamin deficiency should be kept in patients with malnutrition .